Velusetrag for the treatment of chronic constipation. (2nd August 2016) - Bassotti, Gabrio; Gambaccini, Dario; Bellini, Massimo
ABSTRACT: Introduction : Chronic constipation is a frequent complaint in daily clinical practice. Notwithstanding the availability of numerous drugs, its treatment it is still unsatisfactory. However, new emerging treatments are in the pipeline and some drugs seem to be promising; among these velusetrag, a selective 5-HT4 receptors agonist. Areas covered : An in depth Medline literature search was performed concerning topics related to the treatment of constipated patients with velusetrag. In addition, abstracts concerning the topic were searched by hand in our libraries. Expert opinion : After analyzing the available data, the authors feel that velusetrag may likely improve symptoms and the quality of life of chronically constipated subjects. However, additional data is needed to fully understand the safety and efficacy of velusetrag, particularly in patients on long-term therapy. Thanks to the once-daily dosing and the pharmacologic properties, velusetrag could be used as a single agent or in association with other drugs. In the future, this drug holds the potential to be an effective adjunct to the therapeutic armamentarium for chronic constipation.